Efeito do continence App® para promover conhecimento, atitude e prática de puérperas sobre incontinência urinária: ensaio clínico randomizado - Saboia, Dayana Maia (2022)
Urinary Incontinence (UI) affects women at different times of life, causing damage considerable impact on well-being and quality of life. However, the literature reveals limited knowledge, attitude and practice of women on this issue, which points to the need to implement evidence - based strategies to intervene in this situation. The objective was to evaluate the effects of using the Continence App® on the knowledge, attitude and practice of postpartum women in relation to UI. For that, a Randomized Clinical Trial was carried out with two groups, in which one group received the Continence App® as an intervention and the other group received the routine care of the researched institution, in Fortaleza, Ceará. The population consisted of women aged 18 years or older, who were in the median period of vaginal postpartum at physiological term. For data collection, an instrument was used with sociodemographic, gynecological, obstetrical and clinical information and the instrument for assessing knowledge, attitude and practice. Data were collected, even during hospitalization (baseline), in person, through interviews, and 12 weeks after delivery (outcome), by telephone. The primary outcome of the study was the mean score of participants' knowledge, attitude and practice regarding UI. Data were compared using Pearson's Chi-square, Fisher's Exact or Mann-Whitney U tests, with a significance level of 5% and a confidence interval of 95%. The study was approved by the Research Ethics Committee with CAAE 56539116.4.0000.5054 and registered in the Brazilian Clinical Trials Registry database with the primary identifier RBR-5634jr. There were a total of 349 eligible women, however the final sample consisted of 138 postpartum women (GI:74/53.6%; GC:64/46.4%). The total duration of the study was 40 months. At baseline, the groups were similar in relation to all investigated variables, except in relation to participation in educational activities for childbirth and the presence of the complaint of strength to initiate urination, which were more prevalent in the intervention group. Knowledge, attitude and practice was also similar between groups, with the attitude domain presenting the highest scores and knowledge and practice the lowest, respectively. In the period of 12 weeks after childbirth, women who used the Continence App® had more adequate knowledge about UI (GC:08/12.5% x IG:28/37.8%; p=0.001), more specifically about forms of prevention; and better practice score (GC:15.2±30.0 x IG: 25.5±37.5; p=0.041), especially in relation to the adoption of preventive measures. The attitude remained unchanged. There was also a decrease in the impact of UI on daily life (GI/LB: 2.9±4.1 x GI/outcome: 1.6±3.1; p=0.036) and subsequent improvement in the QoL of women in the intervention group (GI/LB: 5.2±6.5 x GI/outcome: 2.7±5.0; p=0.012). The attitude remained unchanged. It is concluded that the Continence App® is able to improve the knowledge and practice of puerperal women about urinary incontinence.